Building A Powerfull File Specification Application For Database System Design - Mohammad Syamsul Azis; Hasan Basri (Universitas Islam Kuantan Singingi, 2024)
The database is a collection of data that is well organized so that the data is easy to store, access and manipulate. Each database can contain all databases, or it can contain any number of database objects, such as files or tables. The purpose of the database was to organize data/organize data so that it is easy to obtain, accurate, and speedy in data retrieval, so that there was no duplication of data and the data is easy to maintain. Database has an important role to build an application. To build an application, valid data is needed so that the data synchronization of the application made with the designed database can be connected so that the data structure and data manipulation that occurs according to needs. The initial stage in making this program is analysis. The analysis was done by designing the program using diagrams. The method used in this research was the prototyping method. The diagrams used are Use Case Diagrams and Activity Diagrams. The result of this research is the application was made according to the needs of the users. In addition to being easy and practical, users found it very helpful because it saved time in making specification files, which were originally quite complicated and took a long time to make, now with this application file specifications could be made easily and quickly.